Single-cell multiomics sequencing reveals the functional regulatory landscape of early embryos - Wang, Yang; Yuan, Peng; Yan, Zhiqiang; Yang, Ming; Huo, Ying; Nie, Yanli; Zhu, Xiaohui; Qiao, Jie; Yan, Liying (Nature communications, 2021)
Extensive epigenetic reprogramming occurs during preimplantation embryo development. However, it remains largely unclear how the drastic epigenetic reprogramming contributes to transcriptional regulatory network during this period. Here, we develop a single-cell multiomics sequencing technology (scNOMeRe-seq) that enables profiling of genome-wide chromatin accessibility, DNA methylation and RNA expression in the same individual cell. We apply this method to depict a single-cell multiomics map of mouse preimplantation development. We find that genome-wide DNA methylation remodeling facilitates the reconstruction of genetic lineages in early embryos. Further, we construct a zygotic genome activation (ZGA)-associated regulatory network and reveal coordination among multiple epigenetic layers, transcription factors and repeat elements that instruct proper ZGA. Cell fates associated cis-regulatory elements are activated stepwise in post-ZGA stages. Trophectoderm (TE)-specific transcription factors play dual roles in promoting the TE program while repressing the inner cell mass (ICM) program during the ICM/TE separation. Extensive epigenetic reprogramming occurs during preimplantation embryo development. Here the authors develop a single cell multiomics sequencing technology that enables profiling of genome-wide chromatin accessibility, DNA methylation and RNA expression in the same individual cell and apply this method to study mouse preimplantation embryos.